Distal Tibiofibular Syndesmosis: Anatomy, Biomechanics, Injury and Management - Yuen, Chi Pan (Open Orthop J, 2017)
A stable and precise articulation of the distal tibiofibular syndesmosis is essential for normal motion of the ankle joint. Injury to the syndesmosis occurs through rupture or bony avulsion of the syndesmotic ligament complex. External rotation of the talus has been identified as the major mechanism of syndesmotic injury. None of the syndesmotic stress tests was sensitive or specific; therefore the diagnosis of syndesmotic injury should not be made based on the medical history and physical examination alone. With the improvement in ankle arthroscopic technique, it can be used as a diagnostic and therapeutic tool in the management of distal tibiofibular syndesmosis injury.